(untitled) (Annual of the Faculty of Philosophy in Skopje, 2024)
This research evaluates the psychometric characteristics of the short version of Generic Conspiracist Beliefs scale (GCB-15) translated in Macedonian language. A convenient online sample of 615 ethnic Macedonians (53.2% women, average age M=30.6; SD=20.4) from 18 cities participated voluntarily in the data gathering process. The translation process involved two independent interpretations, a back-translation, and consensus discussions. The mean scores for GCB-15 subscales were higher compared to other studies, possibly indicating elevated conspiracist beliefs in this population. The results from the exploratory factor analysis suggested a two-factor structure, distinguishing general conspiracist ideation and extraterrestrial beliefs. The confirmatory factor analysis supported this model over one- or five-factor structures. The Cronbach Alpha indices indicated acceptable internal consistency of all subscales (from α=.61 to α=.80) and very high one for the overall scale (α=.91). Convergent validity was confirmed by examining correlations with conspiracist mentality and populist attitudes, while discriminant validity was demonstrated by non-association with emotional intelligence. Criterion-based validity was confirmed by predicting belief in COVID-19 conspiracy theory, whereas known groups’ validity showed differences in GCB based on education, economic status, and life satisfaction, however, the hypotheses were supported only partially. In conclusion, the GCB-15 translated in Macedonian proves to be a valuable instrument for studying conspiracist beliefs in this cultural context, offering additional support for its effectiveness across various cultures.